SLUM, SQUATTER, AND QUASI-SQUATTER HOUSING DEPRAVITY IN YOGYAKARTA - Arap Matinguny Adris, Suratman Worosuprojo, dan M. Baiquni (Jurnal Teknosains, 2014)
This studyaims at deepen our understanding of the slum-squatter housing issue in relation to thedifferences in household socio-economic factors. The theoretical basis of the study comes from literatureon self-help housing,consolidation, and marginality especially by J. Turner and colleagues. Threehousehold factors are key to the processes of taudification and consolidation in this city namely, income,dependency burden, and land tenureship.This studyattempts to synthesise a facility allocation model i.e. a Client-Oriented model; and to establish thetheoretical background of the concept of Self-Help housing advocated by Turner and friends. The study findsout that self-help housing as proposed by these researchers lacks a theoretical and philosophical setting. Inthis context, the study advances the Self-Care Ethic philosophy and a Covering Law theory as the departureof self-help and housing consolidation policies in urban settlements. With this in mind, the Client-Orientedmodel is instrumental because its purpose is to determine the degree of housing and facility in a settlement.